3D Printing of MEMS Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Three-dimensional printing is among the emerging technologies of our time. While it was previously primarily employed for rapid prototyping, this technology has entered a phase of accelerated production, especially for complicated or small objects. Most recently, novel 3D printing technologies have enabled objects with features at the micro- or even nano-scale to be fabricated. Meanwhile, well-known problems such as the waviness of fused deposition modeling (FDM)-printed parts, the missing long-term stability of some typical printing materials or the reduced mechanical properties of 3D-printed objects persist.This Special Issue focusses on all topics related to the 3D printing of micro-electro-mechanical systems (MEMS), such as novel or advanced features enabled by 3D printing compared to conventional technologies, but also the challenges that continue to exist regarding the application of 3D printing technologies for MEMS and new approaches to overcoming them.